Safe sex and women. Issue 1 (February 1992) - Sherr, L; Strong, C
Abstract : OBJECTIVE--Sexual behaviour, condom use, HIV knowledge and anxiety for women were examined to understand the range of sexual behaviours, predictors of safer sex and the extent of relapse. DESIGN--A cross sectional sample of women STD clinic attenders completed interviews and questionnaires. SETTING--Central London STD Clinic. SUBJECTS--153 women drawn from consecutive attenders at a sexually transmitted disease (STD) clinic in inner London. RESULTS--A quarter of the sample had never responded to safe sex and a further 14% had been unable to maintain it over time. Anxiety and knowledge did not differ between safe and relapsed groups, but self efficacy and cognitive variables did. Those who maintained safe sex had significantly less sex. Ten percent of the sample had unprotected anal intercourse. Most women saw themselves in longer term relationships, yet a quarter had sex outside of the relationship and a fifth stated that their partners also did. HIV information gathering was passive and 74% felt they could not protect themselves against infection. High concern over HIV was monitored. Condom uptake was low and non-existent for anal intercourse. 25% had undergone HIV testing. These women did not differ significantly in terms of their behaviour from the untested women. CONCLUSIONS--HIV risks for women are a source of anxiety and tailored intervention is needed to reduce risk and promote dialogue and negotiation.